Google Translate in Tarjamah Learning at Arabic Language Education UIN Walisongo Semarang - Mustolikh Khabibul Umam (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2021)
The development of translator applications in the last decade, has had a significant impact on the results of learning tarjamah to students majoring in Arabic language education (PBA), the ability of translator applications is increasing all the time with improved data retrieval processes and systematic search procedures. A number of Students of PBA UIN Walisongo Semarang consider the application of translation known as Google Translate to be an indispensable tool to save time and effort. However, how this application has a role to play in the process of learning tarjamah. This research is intended to answer the problem: 1) What is the role of Google Translate in the process of translating Arabic text?. 2) What impact does it have on the use of Google Translate apps?. This research is a qualitative research category that is analyzed using statistical techniques with data collection techniques in the form of interviews, questionnaires and also documentation. The data is analyzed using qualitative descriptive analysis strategies and qualitative verification. The results showed that Google Translate has a considerable contribution to the translation process of PBA students. The average test results of questionnaires get more than 56% in several categories, namely in terms of intensity of use, function, effectiveness, how to use, impact of use, efficiency, quality, facilities, benefits, disadvantages and advantages. The use of this machine translator also has an impact on students. The results showed 58% for positive impact and 42% for negative impact on the use of internet-based translation application.